ANALISIS DETEKSI IRIS MATA MENGGUNAKAN METODE DETEKSI TEPI SOBEL - Ayu Fitri Amalia; Handoyo Saputro (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2018)
The data processing of iris detection which was done by computer system were able to get better and eficient information. One of method that was used in digital image processing is edge detection. The function of this method is to identify the line or edge of the image so that the information of border line of image that can be highlighted and applied to identify the iris digital image pattern. In this research, the researcher has been tried an alternative to segment the system in order to identify the iris focused to image processing by edge detection and iris fitur extraction used Sobel detection. Iris image was from Chinese Academy of Science Institute of Automation (CASIA) version 1.0 database. The images were gray level images in BMP format and 320 x 280 pixel. It was consists of 756 images. As the results, 20 selected iris digital images randomly could not be identified by Sobel detection.